Fishes of the Western North Atlantic. - Bigelow, Henry Bryant, 1879-1967; Schroeder, William C. (William Charles), 1895- (Memoir (Sears Foundation for Marine Research), 2018)
"Part Two in the Fishes of the Western North Atlantic series describes the sawfishes, guitarfishes, skates, rays, and chimaeroids that inhabit the waters adjacent to the eastern coastline of North and Central America and the northern portion of South America. Specialist authorships of its sections include detailed species descriptions with keys, life history and general habits, abundance, range, and relation to human activity, such as economic and sporting importance. The text is written for an audience of amateur and professional ichthyologists, sportsmen, and fishermen, based on new revisions, original research, and critical reviews of existing information. Species are illustrated by exceptional black and white line drawings, accompanied by distribution maps and tables of meristic data."--